2017
DOI: 10.18632/oncotarget.16716
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene inhibits inflammation and ROS production in chondrocytes by activating Nrf2 pathway

Abstract: Pterostilbene has been reported as a potential drug to inhibit oxidative stress and inflammation. However, the effect of pterostilbene on chondrocytes and osteoarthritis remains to be elucidated. We sought to investigate whether pterostilbene could protect chondrocytes from inflammation and ROS production through factor erythroid 2-related factor 2 (Nrf2) activation. The pterostilbene toxicity on chondrocytes collected from cartilages of Sprague-Dawley rats was assessed by CCK-8 test. Immunofluorescence and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…Additionally, previous studies showed that activating Nrf2 could attenuate the activation of NF-κB [34]. Furthermore, a large body of studies showed that many natural herbal compounds could inhibit the inflammatory responses of OA by activating the Nrf2 signaling pathway [35,36]. In the present study, our results showed that the expression of Nrf2 and HO-1 were significantly upregulated by morin.…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, previous studies showed that activating Nrf2 could attenuate the activation of NF-κB [34]. Furthermore, a large body of studies showed that many natural herbal compounds could inhibit the inflammatory responses of OA by activating the Nrf2 signaling pathway [35,36]. In the present study, our results showed that the expression of Nrf2 and HO-1 were significantly upregulated by morin.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, pterostilbene down‐regulated the secretions of IL‐6, interleukin‐18 (IL‐18), vascular endothelial growth factor (VEGF), NO, matrix metalloproteinase‐2 (MMP‐2), and matrix metalloproteinase‐9 (MMP‐9) all events that may be correlated with the suppression of LPS‐induced NF‐κB p65 nuclear translocation in E11 cells . Furthermore, pterostilbene was found to be a potent Nrf2 activator that contributes to inhibit IL‐1β‐mediated inflammation in chondrocytes, as well as attenuate immune‐mediated death of pancreatic β cells . In vivo , pterostilbene possesses potential anti‐neuroinflammatory effect through significantly repressing LPS‐induced IL‐6 and TNF‐α mRNA expression in rat hippocampus .…”
Section: The Effect Of Pterostilbene On Aging Biomarkersmentioning
confidence: 99%
“…Treatment with pterostilbene markedly ameliorated inflammatory response, as evidenced by the decrease in proinflammatory cytokines (IL‐1β, TNFα, and interferon gamma (IFN‐γ) in streptozotocin (STZ)‐induced diabetic mice . In an osteoarthritis model, pterostilbene has protective effect on cartilage degeneration by modulating IL‐1β‐mediated inflammation via nuclear translocation of Nrf2 . Pterostilbene improves the survival rate and alleviate polymicrobial sepsis‐induced liver injury in mice is because of suppressed inflammatory response possibly associated with SIRT1 signaling activation .…”
Section: The Effect Of Pterostilbene On Aging Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…PTS on the opposite side rummages NO production in plasma and erythrocyte membrane in NaF-treated rodents because of its antioxidative capacity. PTS prompts the enactment of Nrf2/HO-1 pathway and eNOS phosphorylation in endothelial cells and thus reestablishes the NO level in control condition (Xue et al, 2017).…”
Section: Discussionmentioning
confidence: 94%